Building learnings in Body Language from a WebQuest: A multiple case study - Rocu Gómez, Patricia; Blández Ángel, Julia; Sierra Zamorano, Miguel Ángel (Revista Complutense de Educación, 2019)
The purpose of this study has been to evaluate the level of perceived learning and the general satisfaction with an educational experience that consist of an expressive-corporal educative proposal implemented with WebQuest (WQ) at the Primary, Secondary and University educative levels. It was conceived as a multiple case study in which three teachers with their respective students participated (124 students in total, of 5 class groups). The data were collected using different research instruments: interviews and journals with the teachers while questionnaires and analysis of documents such as blogs, group and individual journals were used with the students. The data were analyzed through a qualitative content analysis using the Atlas.ti software version 7. The quality and credibility criteria of this study were the prolonged time in the research field, the exhaustive and reiterative categorization and analysis followed as well the methodological triangulation of instruments and participants that were employed in the three educational contexts. The conclusions show that the learning competences and objectives designed in the educative proposals have been adequately achieved. Specifically, most of the students and the three teachers perceived that they have learned through the WQs, specifically procedural knowledge of both Body Language (BL) and technology learnings. They were also satisfied with the educational experience developed using this teaching resource.